PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE TPS DENGAN ALAT PERAGA RUBBIK TERHADAP SELF EFFICACY SISWA PADA MATERI KUBUS DAN BALOK - Tri Ratna Rahayu; Miftahul Huda; Ali Shodikin (INSPIRAMATIKA, 2017)
This study aims to determine the effect of cooperative learning model of TPS type with the rubbik props to the students' self efficacy on the material of cube and beam grade VIII MTs Putra-Putri Simo in the academic year 2016/2017. Data collection techniques used were observations in mathematics learning. Data analysis in this research by using difference test mean. Based on the results of the analysis it is known that the samples are nomal and homogeny distributed, and there is influence of cooperative learning model of TPS type with the rubbik props to student self efficacy.